Packaging Liquidity: Blind Auctions and Transaction Efficiencies - Kavajecz, Kenneth A.; Keim, Donald B. (Journal of Financial and Quantitative Analysis, 2005)
Abstract The costs of implementing investment strategies represent a significant drag on the performance of mutual funds and other institutional investors. It is the responsibility of institutional investors, and in the interests of the individual investors they represent, to seek market mechanisms that mitigate trading costs. We investigate an example of one such liquidity provision mechanism whereby liquidity demanders auction a set of trades as a package directly to potential liquidity providers. A critical feature of the auction is that the identities of the securities in the package are not revealed to the bidder. We demonstrate that this mechanism provides a transactions cost savings relative to more traditional trading mechanisms for the liquidity demander as well as an efficient way for liquidity suppliers to obtain order flow. We argue that the cost savings afforded this new mechanism are due to the potential for low cost crosses with the bidder's existing inventory positions and through the longer trading horizon, and superior trading ability, of the bidders. This research suggests that the ability to innovate via new liquidity provision mechanisms can provide market participants with transaction cost savings that cannot be easily duplicated on more traditional exchanges.